MEMBANGUN KOTA RAMAH ANAK DENGAN BUDAYA KOTA BERSERAMBI BACA - Susi Ratna Sari (Kafa`ah: Journal of Gender Studies, 2016)
The citizen run their social activities such as economy, with all economical aspects and dimension. However, it has various types of social problems, as it was faced by children in urban areas. The problems of children are concerned to us all, because those kinds of troubles affect the national quality of a nation. The problems are caused by the limitation both on facilities and institution for managing purposes. Therefore, it is important to consider that the government must build serambi baca (reading place) as the children can take its benefits for reading facilities. By building the well organized programs to help them to deal with the social problem which dominate social phenomenon in the cities, it makes them be able overcome their social problems.